2012
DOI: 10.1021/es2045579
|View full text |Cite
|
Sign up to set email alerts
|

Mercury Distribution across 14 U.S. Forests. Part II: Patterns of Methyl Mercury Concentrations and Areal Mass of Total and Methyl Mercury

Abstract: This study characterized distribution patterns of monomethyl mercury (MeHg) and areal mass of total mercury (THg) and MeHg across U.S. upland forests. MeHg concentrations increased from surface litter (average: 0.14 μg kg(-1)) to intermediate (0.47 μg kg(-1)) and deeper, decomposed litter (1.43 μg kg(-1)). MeHg concentrations were lower in soils (0.10 μg kg(-1) at 0-20 cm depth; 0.06 μg kg(-1) at >20 cm depth). Ratios of MeHg to THg were higher in litter compared to soils. In soils, MeHg concentrations positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
73
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(84 citation statements)
references
References 60 publications
9
73
1
1
Order By: Relevance
“…Few studies have previously reported MeHg data in soil; however, some have reported MeHg/THg, with values as high as 5% [14], but most <1% [4], [6]. Here, we reported values of about 0.5% at FB and close to 1% at MC, consistent with most studies reviewed by Grigal [6] and Obrist [4].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Few studies have previously reported MeHg data in soil; however, some have reported MeHg/THg, with values as high as 5% [14], but most <1% [4], [6]. Here, we reported values of about 0.5% at FB and close to 1% at MC, consistent with most studies reviewed by Grigal [6] and Obrist [4].…”
Section: Discussionsupporting
confidence: 90%
“…Soil in areas with high geogenic Hg concentrations can show the reverse of the typical depth pattern, with greater Hg concentrations in the deep soil than near the surface [15]. Despite the greater Hg concentrations commonly measured in surface horizons, deeper mineral horizons generally store more Hg because of the much greater mass of mineral-dominated subsoil in most landscapes [4], [6], [16]. Total soil storage of Hg can vary from a few mg/m 2 to >50 mg/m 2 , and these values vary, similarly to those of Hg concentrations, as a function of source loads of atmospheric Hg deposition, the amount of SOM in soil, and geogenic concentrations in parent material [3], [6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Total Hg concentrations in these sediment were less than the median Hg level in surficial or modern lacustrine sediments from 20 lakes in forest landscapes of northeastern Minnesota (Engstrom et al, 2007), yet both total Hg and MeHg in GRPO sediment were greater than the median values for 257 stream sediments across the US (MeHg 0.51 ng/g dw, total Hg 30.3 ng/g dw; Scudder et al, 2009). Total Hg in GRPO surficial soils were similar to those measured at nearby Voyageurs National Park, MN (A-horizon range, 58 to 256 ng/g dw; Wiener et al, 2006), while both MeHg concentration and the fraction of total Hg present as MeHg were similar to or higher than those measured in soils of other forest ecosystems (Tabatchnick et al, 2011;Obrist, 2012). As with the streamwater samples, our analyses of GRPO sediments and soils are indicative of an ecosystem with active, substantial Hg methylation.…”
Section: Ecosystem Contamination and Sensitivity To Hgsupporting
confidence: 57%